The Transition to Ophthalmology Residency: A National Survey of the Combined Ophthalmology PGY-1 Program - Azad, Amee D.; Yuan, Melissa; Weinert, Marguerite; Rosenblatt, Tatiana R.; Miller, Joan W.; Lorch, Alice (Journal of Academic Ophthalmology, 2023)
Background In 2017, the Accreditation Council for Graduate Medical Education announced all ophthalmology residency programs would provide a combined transitional or joint preliminary program for first postgraduate year (PGY-1) residents, with mandatory implementation by 2023.Purpose This study aimed to survey ophthalmology residency program directors, postgraduate year 2 (PGY-2) ophthalmology residents who were a part of the first, official combined ophthalmology PGY-1 year, and postgraduate year 3 (PGY-3) residents who were a PGY-1 resident the year prior to integration to evaluate characteristics and perspectives on the combined ophthalmology PGY-1 year.Methods A national, internet survey-based study approved by the Association of University Professors of Ophthalmology (AUPO) was disseminated to the AUPO listserv of program directors (PDs) and PGY-2 and PGY-3 ophthalmology residents from July to August 2022 and then again April to June 2023.Results Twenty-six PDs completed the survey (response rate 20.3% out of 128 PDs). Forty-one PGY-2 ophthalmology residents who underwent the combined ophthalmology PGY-1 year and 33 PGY-3 ophthalmology residents also completed the survey. Most PGY-1 curricula focused on exposure to comprehensive ophthalmology and provided indirect ophthalmoscope, slit lamp, and refraction skills training to residents. Early exposure to fundamentals and clinical workflows were commonly cited benefits to the integration. When PDs were surveyed about how well-prepared PGY-1 residents who went through the combined year are for the PGY-2 relative to the prior year's class, 16 (61.5%) responded “better prepared.” PGY-2 residents also reported a relatively higher level of clinical preparedness and familiarity with ophthalmology co-residents than PGY-3 residents. Several areas of improvement cited by both PDs and residents were identified including a dedicated didactic curriculum and more time in ophthalmology during the PGY-1 year.Conclusions We found an overall net benefit from the integration of the combined ophthalmology PGY-1 year. Benefits include early exposure to clinical skills and knowledge specific to ophthalmology, leading to increased confidence and preparedness for the rigorous transition to ophthalmology residency. We also identified many areas for improvement to optimize the PGY-1 year including a formal curriculum and additional time in ophthalmology. Programs should work closely with their residents, faculty, and non-ophthalmology PDs to refine the PGY-1 for the benefit of future ophthalmologists.
Keywords: combined ophthalmology intern year; preparedness; ophthalmology residency; early exposure; ophthalmology experience